Different methods of managing bluestem pastures - Smith, E.F.; Owensby, Clenton E.; Kolstad, S.P. (Kansas State University. Agricultural Experiment Station, 2011)
Studied were the effects of early season heavy stocking and burning on cattle performance, productivity of pastures and range condition as determined by plant population changes. The objective of early season heavy stocking at twice the normal rate for the first half the growing season is to obtain more gain per acre, have cattle available for dry lot finishing at mid summer and determine if the grass will recover the last half of the season. Forage quality is best early in the growing season.
Keywords: Beef; Cattle performance; Range condition; Forage quality